Penyuluhan Pemahaman Makan Olahan Ikan Sebagai Upaya Peningkatan Gizi Anak di Daerah Gampong Cot Unoe - Rahmi Rahmi; Sufitrayati Sufitrayati; Nelly Nelly; Agustin Nurhayati; Munawarah Munawarah; Mai Simahatie; Bayu Eko Broto; Elvina Elvina; Sri Murniyanti (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Health efforts for children can be made through improving nutrition. Good nutrition will produce quality human resources. One of the important nutrients for the growth and development of school children is protein from fish. This service activity conveys the message of the importance of fish consumption, involves the role of parents in transforming the benefits of sustainable fish consumption, and explores the factors that influence children's consumption of fish. So it is hoped that it can increase the target's knowledge and determine the factors that influence the target in consuming fish. The results of this activity concluded that there had been an increase in the target group's knowledge about the importance of fish consumption, but its implementation in daily practice could not yet be confirmed. So it is necessary to monitor its implementation. Knowledge and motivation are not the main factors for children wanting to consume fish, the availability of food made from fish at home and processing that can increase children's interest in consuming fish are the main factors that need to be considered.